Pre-service English teachers level of grittiness, academic achievement, and BLEPT performance - Agron, Ryan Jay Oania (Studies in English Language and Education, 2025)
This retrospective-predictive study examined pre-service English teachers level of grittiness, College Academic Achievement (CAA), and performance in the Board Licensure Examination for Professional Teachers (BLEPT). The respondents level of grittiness was measured using an adapted instrument. CAA was based on their General Weighted Average (GWA), as reflected in their Transcript of Records (TOR). BLEPT ratings were provided by the respondents themselves as released by the Professional Regulation Commission (PRC). The gathered data were analyzed using Pearson r and stepwise multiple regression. The findings revealed that the respondents moderate level of grittiness has no relationship with their barely passing BLEPT rating, while their CAA has a moderately negative association with it. The inability of their CAA to depict their BLEPT performance raises issues about the quality of their teacher education training prior to taking the BLEPT. Moreover, their BLEPT performance was significantly predicted by their CAA alone. Passion and perseverance, which are important qualities of a teacher, were not found to be significant predictors. The results indicate that it is still competent initial teacher education preparation that has the magnitude to determine BLEPT success. This denotes the need for intellectually enriching instruction, especially in the field of specialization, and an evaluation mechanism based primarily on students scholastic performance so that Teacher Education Institutions (TEIs) are in a better position to gauge whether their retention policies ensure quality assurance through their licensing performance.